PHENOMENOLOGICAL STUDY OF LOCAL FINANCIAL MANAGEMENT WITH THE LOCAL GOVERNMENT INFORMATION SYSTEM (SIPD) IN THE CITY GOVERNMENT OF SURAKARTA - Ika Diah Purwati; Witono, Banu; Zulfikar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The purpose of this phenomenological qualitative study is to explore the subjective meanings and experiences of actors in regional financial management during the implementation of the Regional Government Information System (SIPD) of the Surakarta City Government. Data were collected through interviews, observations, and document studies with six informants. Data reduction, data presentation, and conclusion drawing were some of the analytical methods used. The study findings show that, although some informants had different opinions about how well financial management was functioning, SIPD was generally considered effective in improving transparency and accountability. This mechanism is very important for integrating planning and reporting. There are still technical obstacles, such as server disruptions. Tiered assistance and Technical Guidance (BIMTEK) were used to strengthen the implementation method. Synergy between SIPD and human resource skills is essential to improve efficiency. Stakeholders expect future SIPD development to be more robust, comprehensive, and supportive of overall digital change.